PENGARUH INTENSITAS MENONTON SINETRON REMAJA TERHADAP PERILAKU MORAL ANAK USIA 5-6 TAHUN (STUDI EX POST FACTO DI KELURAHAN KELAPA GADING TIMUR, JAKARTA UTARA) - Rizki Fitrianti (Al Hanin, 2021)
AbstrackThis study aims to determine the effect of the intensity of watching teen soap operas on the moral behavior of children aged 5-6 years in the Kelapa Gading Timur Village, North Jakarta. The research method used is the Ex Post Facto method. The sampling technique used cluster random sampling and simple random sampling with a total sample of 30 children.The data analysis technique used for hypothesis testing is the t-test after first testing the requirements consisting of normality test and homogeneity test. The results of hypothesis testing with t-test obtained tcount of 10.392, while ttable of 2.25 so 10.392 2.25, and a significance level of 0.00 with an alpha error rate of 0.05 then 0.00 0.05 so that based on the statistical hypothesis H0 is rejected and Ha is accepted, meaning there are differences in moral behavior children in the high intensity group watching teen soap operas with the moral behavior of children in the low intensity group watching teen soap operas. The results showed that the moral behavior of children in the high intensity group watching teen soap operas would be lower than the moral behavior of children in the low intensity group watching teen soap operas. The implication of this research is the role and supervision of parents on teen soap operas that are watched by children. Parents must guide and give signs in watching television. Parental control in the selection of television shows will be a preventive measure so that children are not mistaken in choosing television shows to watch.Â Keywords: Teenage soap operas, moral behavior of children aged 5-6 years